تطبيق لعب الاسرار المتسلسل في ترقية استيعاب المفردات في المدرسة الثانوية الإسلامية المعارف دورنسيوو بانداءن - Indah Hayati; Syaifullah Syaifullah (Universitas Yudharta Pasuruan, 2019)
The study was backed by the low level of mastery of the vocabulary students in the Islamic Senior High School at Durensewu Pandaan. This is because at the time the process of teaching and learning, students tend to get bored and less excited. And from less passion for the students in the teaching and learning process to follow, so students are less controlled vocabulary. This research uses a quantitative approach and use experimental methods, using techniques of t-test to find out the significant effects of the application of the language game in the from of serial whispered against the level of mastery of the vocabulary of arabic studetns levels of trust with α = 0,05 or 5%. Based on the results of hypothesis testing that has been done (t-test) that 7,612 > 2,898, so Ho rejected. So there are significant differences in the level of mastery of Arabic vocabulary. In accordance with the results of the test of the t-test, then the use of the game were shown to influential chain significantly towards mastery of the vocabulary of students.